2018
DOI: 10.2147/ijn.s182384
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated delivery of functionally active miRNA-142-3p inhibitor reduces tumorigenicity of breast cancer in vitro and in vivo

Abstract: BackgroundExosomes, widely recognized natural nanovesicles, represent one of the recently discovered modes of intercellular communication due to their ability to transmit crucial cellular information that can be engineered to have robust delivery and targeting capacity. MiR-142-3p, one of the upregulated microRNAs (miRNAs) in many types of breast cancer, activates the canonical Wnt signaling pathway and transactivates the miR-150 expression, and results in the hyperproliferation of cancer cells in vitro and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(132 citation statements)
references
References 45 publications
1
130
0
1
Order By: Relevance
“…MSC-EVs may act as biological delivery platforms able to shuttle therapeutic molecules, such as miRNAs. Further, MSC-EV cargo may be engineered by either exogenous load [4] or reprogramming of the secreting cells [5,6], making direct load comparison an imperative challenge. From this perspective, a reliable normalization approach to select stable EVs-related miRNA RGs is mandatory and, to date, only few methods have been validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC-EVs may act as biological delivery platforms able to shuttle therapeutic molecules, such as miRNAs. Further, MSC-EV cargo may be engineered by either exogenous load [4] or reprogramming of the secreting cells [5,6], making direct load comparison an imperative challenge. From this perspective, a reliable normalization approach to select stable EVs-related miRNA RGs is mandatory and, to date, only few methods have been validated.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, by avoiding the concerns of using live and replicating cells that may undergo mal-differentiation or mutation, the idea of EVs as therapeutics is being explored, since they can mimic several biological actions of MSCs [1] through embedded lipids, proteins, mRNAs and miRNAs [2,3], therefore acting as biological nanocarriers. Even more intriguing, MSC-EVs may be engineered by either exogenous load [4] or reprogramming of the secreting cells [5,6] to shuttle and deliver specific and therapeutic molecules, such as miRNAs or mRNAs, eventually driving the focused influence on target cells [7]. As an example, in the orthopedic field, which is one of the most actively studied areas in regenerative medicine, miRNA-enriched MSC-EVs were shown to promote cartilage regeneration [5,6] by modulating ECM production.…”
Section: Introductionmentioning
confidence: 99%
“…These UC-MSC-exosomes reduced proliferation of human osteosarcoma 143B and mouse osteosarcoma K7M2 cells in vitro in a dose-dependent manner by inducing apoptosis. The tumor-homing of MSC-exosomes has been successfully adopted to deliver therapeutic miRNAs to reduce tumors in xenograft mice with patient-derived pancreatic cancer [45], and syngeneic breast tumors in mice [90]. Interestingly, beyond organotropism of tumor exosomes, generalized tropism of tumor exosomes toward neoplastic tissues from different types or species have also been reported [106].…”
Section: Tumor-homing Of Exosomesmentioning
confidence: 99%
“…These exosomal RNAs (miRNAs, modified miRNAs and shRNAs) are fully functional when incubated with recipient cells and lead to target gene knockdown [11]. For example, Naseri et al demonstrated that MSCs-derived exosomes could be used as viable nanocarriers to deliver drug molecules, such as locked nucleic acid (LNA) modified anti-miR-142-3p oligonucleotides to inhibit miR-142-3p expression levels in vitro and in vivo in breast cancer [34]. Using a quantitative RT-PCR approach, we demonstrated that mature lentivirus-encoded antagomiR-4450 were secreted by lentivirus-infected hPLMSCs through exosomes.…”
Section: Discussionmentioning
confidence: 99%